Analysis of Thioredoxins and Glutaredoxins in Soybean: Evidence of Translational Regulation under Water Restriction - María Martha Sainz; Carla Valeria Filippi; Guillermo Eastman; José Sotelo-Silveira; Omar Borsani; Mariana Sotelo-Silveira (MDPI AG, 2022)
Soybean (Glycine max (L.) Merr.) establishes symbiosis with rhizobacteria, developing the symbiotic nodule, where the biological nitrogen fixation (BNF) occurs. The redox control is key for guaranteeing the establishment and correct function of the BNF process. Plants have many antioxidative systems involved in ROS homeostasis and signaling, among them a network of thio- and glutaredoxins. Our group is particularly interested in studying the differential response of nodulated soybean plants to water-deficit stress. To shed light on this phenomenon, we set up an RNA-seq experiment (for total and polysome-associated mRNAs) with soybean roots comprising combined treatments including the hydric and the nodulation condition. Moreover, we performed the initial identification and description of the complete repertoire of thioredoxins (Trx) and glutaredoxins (Grx) in soybean. We found that water deficit altered the expression of a greater number of differentially expressed genes (DEGs) than the condition of plant nodulation. Among them, we identified 12 thioredoxin (Trx) and 12 glutaredoxin (Grx) DEGs, which represented a significant fraction of the detected GmTrx and GmGrx in our RNA-seq data. Moreover, we identified an enriched network in which a GmTrx and a GmGrx interacted with each other and associated through several types of interactions with nitrogen metabolism enzymes.